Faktor – faktor yang Berpengaruh terhadap Nilai Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2015-2020 - Suci Valiani Mumpuni; Maryono Maryono (Owner : Riset dan Jurnal Akuntansi, 2022)
The manufacturing industry in Indonesia is developing quite rapidly, this is evidenced by the increasing number of companies that have been listed on Indonesian Stock Exchange. The Indonesian Ministry of Industry noted that until 2019 there were 639 companies belonging to the various industrial sectors, both medium and large scale. The COVID-19 pandemic has caused the cessation of a number of companies in the various industrial sectors, ranging from factories that stopped their operations and employees who were forced to be laid off. This can lead to a decrease in the company’s performance. Therefore, financial managers are required to further improve financial performance, because through good financial performance a company will become a major consideration for investors. Firm value is the result of corporate performance in a certain period of time. The aim of this research is to analyse the effect of the firm size (SIZE), profitability (ROE) and dividend policy (DPR) on firm value. The data source in this research is sourced from the financial statement of the various industrial sector in manufacturing companies  listed on Indonesia Stock Exchange (BEI) period 2015-2020. Population used in this reasearh is various industrial sector in manufacturing companies. This research uses a quantitative approach with purposive sampling method. Total sample as many as 111 samples. Data processing in this research using the IBM SPSS Statisctic version 22 software. Data analysis tools used in his research is descriptive analysis and multiple regression analysis. The result of this research show that the firm size has no affect on firm value. Profitability has positive affect on firm value. Dividend policy has no affect on firm value.